2016
DOI: 10.1016/j.eswa.2016.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Data quality assessment of maintenance reporting procedures

Abstract: Today's largest and fastest growing companies' assets are no longer physical, but rather digital (software, algorithms. . . ). This is all the more true in the manufacturing, and particularly in the maintenance sector where quality of enterprise maintenance services are closely linked to the quality of maintenance data reporting procedures. If quality of the reported data is too low, it can results in wrong decision-making and loss of money. Furthermore, various maintenance experts are involved and directly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 100 publications
0
18
0
1
Order By: Relevance
“…The work is very interesting, particularly for its explanation of how CMMS can be applied to total productive maintenance (TPM), with over 60 manufacturing companies being considered. There are other notable and excellent presentations on CMMS use in manufacturing and allied company maintenance activities in the literature [2], [27]- [29]. Apart from chronicling the efforts made in applying CMMS to maintenance planning, the geographical spread of those publications and examples provide handy material for researchers who are interested in the proper information management of maintenance systems.…”
Section: Overview Of Cmms Application In Maintenance Managementmentioning
confidence: 99%
“…The work is very interesting, particularly for its explanation of how CMMS can be applied to total productive maintenance (TPM), with over 60 manufacturing companies being considered. There are other notable and excellent presentations on CMMS use in manufacturing and allied company maintenance activities in the literature [2], [27]- [29]. Apart from chronicling the efforts made in applying CMMS to maintenance planning, the geographical spread of those publications and examples provide handy material for researchers who are interested in the proper information management of maintenance systems.…”
Section: Overview Of Cmms Application In Maintenance Managementmentioning
confidence: 99%
“…Data quality dimensions, such as accuracy, accessibility, relevance, completeness and timeliness, depend on the task the data is used for and their relative importance may change as work requirements change (Strong et al, 1997). In maintenance data context, Aljumaili et al (2018) used a set of 12 attributes (Completeness, Metadata constraints, Accuracy, Source reputation, Relevancy, Amount of data, Usability, Conciseness, Availability, Navigation, Security, Up to date) whereas Madhikermi et al (2016) identified the three most important attributes: believability, completeness and timeliness. The latter set is also used in this thesis.…”
Section: The Main Rq Of This Dissertation Is: What Factors Influence mentioning
confidence: 99%
“…However, there remains data that is difficult and expensive, if not impossible to acquire automatically. Manually collected data is required to supplement the vast amounts of automatically produced data in service provision and data-centric decision making (Madhikermi et al, 2016). Examples of such data are operational and cost related data from service operations, such as hours spent on maintenance tasks and spare parts used (Unsworth et al, 2011) or the reasons for an equipment not running (waiting for service, waiting for spare parts, or redundancy; Publication II).…”
Section: Publication V: Introducing User Experience In Manual Data Comentioning
confidence: 99%
“…Madhikermi and his colleagues stress that the quality of enterprise maintenance services are closely linked to the quality of maintenance data reporting procedures. They propose the development of a maintenance reporting quality assessment (MRQA) dashboard enabling any company stakeholder assess/rank company subsidiaries in terms of maintenance reporting quality (Madhikermi et al 2016). Roy and his colleagues present advanced computing and visualisation technologies (like 3D scan and computer tomography data analysis systems) that will improve efficiency of the maintenance and reduce through-life cost of the product.…”
Section: State Of the Artmentioning
confidence: 99%